Kebutuhan Media Pembelajaran Sejarah Interactive Multimedia Instructional di SMA - Mutiara Eka Alhadisti; Ridho Bayu Yefterson (Jurnal Kronologi, 2023)
Media is a learning tool that plays an important role in the learning process. However, the media used by teachers at Baiturrahmah Padang High School is not yet interactive. This makes students bored and choose to play cellphones or chat during the learning process. Students are not enthusiastic in learning history because they do not get a real visualization of the historical material being studied. This study aims to analyze the needs of interactive multimedia instructional as a learning medium in high school for class XI students. This study uses qualitative methods with data collection techniques using observation and interviews. The data obtained was then analyzed in four stages, namely 1) data analysis, 2) data reduction, 3) data presentation, and 4) data verification. The results and discussion obtained from this study are 1) performance gap, where a problem occurs in the history learning process, 2) student analysis, students need media that can visualize real historical events, 3) teacher analysis, teachers need media interactive learning, 4) curriculum analysis; IC; KD; indicator; materials, and historical learning objectives that fit the interactive multimedia instructional. The conclusion obtained is that interactive multimedia instructional is needed as a medium for learning history in high school. Media merupakan sarana pembelajaran yang berperan penting dalam proses pembelajaran. Namun, media yang digunakan guru di SMA Baiturrahmah Padang belum bersifat interaktif. Hal ini membuat siswa bosan dan memilih bermain HP atau mengobrol selama proses pembelajaran berlangsung. Siswa tidak antusias di dalam belajar sejarah karena tidak mendapatkan visualisasi secara nyata dari materi sejarah yang dipelajari. Penelitian ini bertujuan untuk analisis kebutuhan interactive multimedia instructional sebagai media pembelajaran di SMA bagi siswa kelas XI. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data yang menggunakan observasi dan wawancara. Data yang didapatkan kemudian dianalisis dengan empat tahapan yaitu 1) analisis data, 2) reduksi data, 3) penyajian data, dan 4) verivikasi data. Hasil dan pembahasan yang didapatkan dari penelitian ini adalah 1) gap kinerja, dimana terjadi suatu masalah di dalam proses pembelajaran sejarah, 2) analisis peserta didik, peserta didik membutuhkan media yang dapat memvisualisasikan peristiwa sejarah secara nyata, 3) analisis guru, guru membutuhkan media pembelajaran yang interaktif, 4) analisis kurikulum; KI; KD; indikator; materi, dan tujuan pembelajaran sejarah yang pas dengan interactive multimedia instructional. Kesimpulan yang diperoleh adalah interactive multimedia instructional dibutuhkan sebagai media pembelajaran sejarah di SMA.